Pengembangan Model Pengelolaan Komunikasi Di Sekolah Alam (Studi Kasus pada Komunitas Adat Terpencil (KAT) di Sungai Dahan Desa Muara Kilis Kecamatan Tengah Ilir Kabupaten Tebo-Provinsi Jambi) - NOVALINA, Sesti (2015)
The purpose of this research to describe the communication management which is done on the Traditional Corner Communities through the school of nature and development of communications made on Traditional Corner Communities through natural school in the Dahan river, Muara Killis village, Middle District of Ilir, Tebo-Province of Jambi. This research used a qualitative method with evaluative design. The used of the data are primary and secondary data. The sources of the data are the key of informant (LSM), informant (KAT societies), and the new informant (stakeholder which are include), events and activities. The techniques collections of the data are by the interview, observation, and document analysis. The techniques analyses of the data are by the analysis of taxonomic and componential. The validities of the data are by credibility, transferability, dependability and conformability. Based on these results, it can be concluded that: 1) Management Communication which is done on the Traditional Corner Communities through the School of Nature: a) Provide communication services on the Traditional Corner Communities, it is done from the material to the media which is used in teaching (Teaching and Learning). Communication and inter-personal interrelationships, b) the role of educators on providing communication lesson to the usual subjects understood by KAT, they demanded the creative and innovative in delivering materials and demonstrating the media of communication, c) interest on learning in Traditional Corner Communities when receiving communication lessons but lately they began to accept and interested. 2) Development of Communication which is done on Traditional Corner Communities through the School of Nature: a) the difficulties encountered when developing communication through local language and Indonesian on Traditional Corner Communities, the teacher should mastered the KAT dialect then translated into English and Indonesian language for developing KAT student. b) The educational facilities should be provided to support the communication ability at KAT by communication media such as textbooks, picture/drawing ,television and others equipment. The intellectual effort of the traditional corner island is done in many ways and methods.